Successful treatment of a rare giant right atrium aneurysm in an 8-year-old child: a case report - Ekaterina Amansakhatova; Timur Khapaev; Ivan Murashov; Serezha Manukian; Dariya Pogrebnitckaya; Yuriy Kulyabin; Bahram Kamangari; Ilya Soynov (The Egyptian Heart Journal)
Abstract Background Among the various paediatric congenital heart disease pathologies, aneurysm of the right atrium represents a relatively uncommon condition and is characterised by a variety of progressive rhythm irregularities. While a number of cardiac surgical institutions advocate for medication in such cases, others persist in supporting radical surgical correction. Case presentation This paper presents a clinical case in which radical surgical correction was successfully performed on a rare large aneurysm of the right atrium, associated with supraventricular tachycardia, in an 8-year-old patient. Conclusions An aneurysm of the RA is an extremely rare cardiac anomaly with a variable clinical presentation. Despite the availability of a conservative treatment approach, surgical correction remains the preferred option at the majority of cardiac surgery centres. This is not only to prevent the development of complications but also to achieve successful correction of RA aneurysms.